Light microscopy of proteins in their ultrastructural context - Ons M’Saad (Nature Portfolio, 2020)
Imaging specific proteins in the ultrastructural context largely relies on correlative light/electron microscopy, but fluorophore incompatibility and registration issues limit its use. Here the authors develop an expansion microscopy method with pan-labeling of the proteome to obtain EM-equivalent light microscopy images.